Gus Durâ€™s IjtihÄd Paradigm of Contemporary Fiqh in Indonesia - Dahlan, Moh.; Baidlawy, Zakiyuddin; Sugiono, Sugiono (Al-Ahkam, 2019)
This paper reveals Gus Dur's ijtihÄd paradigm of contemporary fiqh in Indonesia in answering the problems of life. This study is a type of library research by tracing Gus Dur's works, Gus Dur's thought studies and other related scientific studies. This research uses the approach of Milton K. Munitz's thinking and the frame of mind â€˜Abd al-MajÄ«d al-NajjÄr. This research found that the conservative ijtihÄd paradigm has led to conservative fiqh which is unable to establish dialectics between fiqh norms and socio-cultural and humanitarian values, which can even lead to radical Islamic movements and acts of terrorism. Therefore, Gus Dur's contemporary jurisprudential ijtihÄd paradigm is needed to build this dialectic. Theoretically, the Gus Dur ijtihÄd paradigm has characteristics promoting different socio-cultural and humanitarian values from Islamic reformers. In practical terms, the Gus Dur ijtihÄd paradigm has made Indonesian socio-cultural values a consideration in understanding and applying contemporary fiqh without changing existing fiqh norms. Gus Dur's contemporary fiqh has also become the basis for maintaining the Pancasila ideology, the 1945 Constitution, the Unitary State of the Republic of Indonesia and Unity in Diversity.